Construction of a Teaching Paradigm for "Comprehensive Ideological and Political Education" in Higher Vocational Engineering Departments under a Virtual-Real Integration Environment - Jin, Weiwei (Journal of Educational Theory and Practice, 2026)
Under the dual background of improving the quality of vocational education and the wide application of virtual and real integration technology, the " big ideological and political course " of higher vocational engineering department, as the key carrier to implement the fundamental task of establishing morality and cultivating people, still faces the practical difficulties such as the disconnection between ideological and political education and professional teaching, the lack of teachers ' quality and the poor adaptability of resources, which is difficult to adapt to the cognitive characteristics and training needs of engineering students. This paper uses literature research method and practical analysis method to systematically sort out the current situation of the integration of virtual and real integration technology and the ' big ideological and political course ' of higher vocational engineering department, and clarify the core crux of the current teaching dilemma. On this basis, following the principles of professional adaptation, virtual and actual coordination, and people-oriented education, the teaching paradigm of " three layers, two environments and one evaluation " is constructed, and its core concept, educational objectives and overall framework are clarified. The implementation path of resource construction, model innovation, and teacher improvement and supporting safeguard measures at the institutional, technical, and collaborative levels are proposed. The research results show that the paradigm can effectively break the barriers between ideological and political education and professional teaching, realize the coordinated promotion of value guidance, skill training and quality improvement, and provide a practical scheme for the high-quality development of " big ideological and political course " in higher vocational engineering department.